PARTISIPASI PUBLIK DI MEDIA SOSIAL (ANALISIS ISI PADA KOLOM KOMENTAR LAMAN FACEBOOK E100SS DALAM ISU TRANSPORTASI PUBLIK) (The Commercium, 2023)
Suara Surabaya is one of the public media that has been around for a long time since 1995. The aim of this study is to observe how public participation occurs in the current technological age. The study focused on how people reacted to Suara Surabaya Facebook accounts as they responded to the public policy on public transport issued by the Surabaya city government. It is important to make public participation in order to know how the participation of the dominant society at a time the government provides information with the reaction of the public. The focus of the research is the comments posted on the Facebook site of Suara Surabaya. This research uses the qualitative content analysis method. The source of the data for this study comes from public comments on the Facebook post of Suara Surabaya about public transport news. The analysis uses the participation form designed by Pusvita dkk. Where it contains six forms of participation, i.e. support, advice, criticism, complaints, reports and knowledge sharing The results of this study found that comments on the participation patterns found in this study are citizens tending to provide support to leading figures such as the mayor of Surabaya or the governor of eastern Java, while for criticism and complaint many are directed to government agencies.